Study of the Façade of the Cilegon Islamic Center Building - Andri Robianto; Husna Izzati (Jurnal Arsitektur Archicentre, 2024)
The Ciegon Islamic Center was founded as a center for Islamic education,boarding, research, and culture.The Ciegon Islamic Center has an Islamic architecture concept. The aim of the research is to determine the application of Islamic architecture in Islamic-style buildings. The method used uses qualitative methods through observation stages. The Ciegon Islamic Center has an Islamic architecture concept. On the building façade, there are elements of door & window facades,walls, roofs, and sun shading. The aim of the research is to determine the application of Islamic architecture to the Ciegon Islamic Center building. The ornaments in the cilegon Islamic center building apply ornaments that are permitted in Islamic buildings, such as geometric shapes,plant tendrils,stars, honeycombs, and calligraphy.Islamic architecture contains the essence and values of Islam, which can be applied, and does not utilize modern building technology as a tool for expressing the essence and values of Islam. An interesting application of the concept of Islamic architecture is found in the building façade in the form of ornament. Which makes the building an Islamic center. To be interesting and have its own special feature